Factores agronomicos en la asociacion frijol-maiz - Tejada, G; Davis, J.; García, S. (International Center for Tropical Agriculture, 1979)
The methodology used and the results obtained are discussed for an investigation conducted at CIAT on agronomic factors of maize- bean associations: planting method, density and date, stakes used, fertilization and cultural practices. It was concluded that if high technological levels are used, there are no differences in bean yields with the different planting methods. Climbing beans give increased yields up to 120,000 plants/ha and bush beans up to 240,000 plants/ha in monoculture and in association. The optimum planting date for beans and maize under CIAT conditions, is generally simultaneous for habits II, III and IV; for growth habit I, beans should be planted 5 days before maize. Bush beans in association yield 30 percent less and climbing beans, 50 percent less than in monoculture. Maize height is sufficient to be used as stakes in climbing bean production. (CIAT)